The impact of terrorism on the Nigerian economy and the Islamic solution (2017)
The conventional wisdom in economic analysis postulates an inverse relationship between social conflicts/terrorism and economic growth and development because the higher the level of insecurity, the more problematic for the society to succeed economically. This paper investigates the impact of social conflicts/terrorism on Nigeria's economy using traditional economic measures subjected to trend and econometric analysis to respectively discern the relationship in terms of magnitude and direction. Secondly, the paper establishes that this negative outcome is predicted by the Islamic perspective which strongly suggests a direct association between peace and economic growth and development in such Quranic verses as Q7:85 and Q8:25, both of which advocate peaceful coexistence, corruption- and violence-free human interactions for best outcomes. Interestingly, most terrorist actions based on Islamic religious justification are acts of corruption condemned by Islam which offers both terrestrial and celestial penalties for the simple reason that social strife disrupts socio-political and economic life.